Two small boys and two teenagers on a slide - Unknown:::Creator::::::::::::
Photograph shows two small boys posing on the ladder of a playground slide. There is a teenage girl sitting on the top of the slide in front of the boys and another standing on the ladder behind the boys. This is probably part of the Campbell Y-Teens Camper Counselor Recreation Program in 1962.